2011
DOI: 10.1016/j.humov.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and visual information do not affect self-paced bilateral finger tapping in children with DCD

Abstract: Children with Developmental Coordination Disorder (DCD) are more variable in timing their fingers to an external cue. In this study, we investigated the intrinsic coordination properties of self-selected anti-phase finger tapping with and without vision and audition in children with and without DCD and compared their performance to that of adults. Ten children with DCD (Mean age = 7.12 ± 0.3 years), ten age-and sex-matched typically developing (TD) children, and ten adults participated in this study. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…The present study agrees with Grillo et al [28] and Rocha et al [40] research. They found that audition manipulation did not change the subjects' performance [28,40].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study agrees with Grillo et al [28] and Rocha et al [40] research. They found that audition manipulation did not change the subjects' performance [28,40].…”
Section: Discussionsupporting
confidence: 94%
“…This result shows that proprioceptive information plays an essential role in the central nervous system for keeping posture [17]. The present study agrees with Grillo et al [28] and Rocha et al [40] research. They found that audition manipulation did not change the subjects' performance [28,40].…”
Section: Discussionsupporting
confidence: 93%
“…3,4,13,27,28 For example, studies found that deficiencies in auditory/visual processing lead to difficulties in rhythm and timing experienced by children with DCD, [29][30][31] as expressed in finger tapping performance of children with DCD which was less accurate and more variable in frequency and coordination. 27 Hence, SPD may impair the ability to correct errors in position, and to modulate acuity, velocity, and force of movement. 23,26,32 Problems in the modulation and integration of sensory input coming from the vestibular, proprioception, visual and auditory systems may reduce motor performance, and mainly balance and manual dexterity.…”
Section: Discussionmentioning
confidence: 99%
“…Movement sensitivity as well as low energy (difficulties in processing proprioceptive information) significantly predicted lower Manual Dexterity in which acuity is heavily dependent on adequate postural control and proper feedback that comes from the proprioceptive system. Roche et al 27 claimed that children with DCD present inaccurate movements since they are either not aware to the sensory information to detect errors or they do not use sensory feedback to correct their motor actions.The present study also found that reduced balance performance was predicted by elevated auditory/visual sensitivity. This supports previous reports that highlight the significant role of difficulties in the visual and auditory processing to the motor coordination difficulties of individuals with DCD.…”
mentioning
confidence: 99%
See 1 more Smart Citation